EFICACY OF ZINC SUPLEMENTATION AS ADJUVANT THERAPY IN CHILDREN 6- 60 MONTHS OLD WITH PNEUMONIA - Sidiartha, I Gusti Lanang; Gede Suandi, I Kompiang; Subanada, Ida Bagus; Siadi Purniti, Ni Putu; Karsana, AA Raka (Medicina; Vol 43 No 1 (2012): Januari 2012)
Morbidity and mortality rates of childhood pneumonia is still high, especially in developing countries. Many efforts are done to decrease the morbidity and mortality rate and one of them is zinc supplementation as adjuvant therapy. The aim of the study is to find the effectiveness of zinc supplementation as adjuvant therapy in childhood pneumonia. The randomized controlled trial study was done on 33 patients with pneumonia at Sanglah Hospital Denpasar. Intervention group received 20 mg zinc elemental each day. Time for recovery and length of hospital stay were compared between zinc and placebo groups. The different was significant if the P value < 0.05. Time for recovery in zinc group and placebo group was 4 days and 3.4 days, respectivelly. Length of hospital stay was 5.9 days in zinc group and 5.6 days in placebo group. The different was not significant. Conclusion is zinc supplementation as adjuvant therapy in childhood pneumonia is not effective to decreased the time for recovery and length of hospital stay. (MEDICINA 2012;43:9-14).
Keywords: zinc supplementation, pneumonia, length of stay